Physical and psychological violence in dating with stress among adolescents during the COVID-19 pandemic - Suci Musvita Ayu; Liena Sofiana; Nurul Karina Sabrina (International Journal of Public Health Science (IJPHS), 2021)
Currently, the juvenile delinquency trend is still very high. Dating violence (DV) is one of the delinquencies that teenagers often commit. DV has negative impacts in the form of physical and psychological impacts. Physical impacts can include bruises, fractures. Meanwhile, the psychological impact can be a the form of depression, stress, anxiety, and sleep problems. This study aimed to analyze the relationship between physical and psychological violence in dating stress adolescents. This study used a cross-sectional design. Sample of this study was 314 students (15-19 years) in Bantul chosen through a purposive sampling technique. Data analysis was using multiple logistic regressions. The results showed that there was a significant relationship towards stress, namely gender (p-value=0.050), physical violence (p-value=0.000), and psychological violence (p-value=0.000). Age (p-value=0.653) and parents' income (p-value=0.100) had no significant relationship to stress. Psychological violence variable (p-value=0.000; OR=6.285, 95%; CI=3.683-10.726) was the most dominant in triggering stress in adolescents. So, there were relationships between gender, physical and psychological violence in dating with the incidence of stress among adolescents in Bantul Regency, Yogyakarta, Indonesia during the COVID-19 pandemic.